Analysis Of The Quality Of Tilapia Meatballs Produced From The Addition Of Seaweed As A Thickener - Rahma Fatiha Asri; Anni Faridah (Universitas Negeri Padang, 2021)
Eucheuma cottonii type seaweed is a rubber material because it has the ability to form a gel, so it can be used as an alternative to thickening agents in the manufacture of fish balls because it is easier to obtain and more efficient. This study aimed to analyze the quality of tilapia meatballs with the addition of 0%, 30%, 40% and 50% of seaweed for organoleptic tests on shape, color, aroma, texture and taste. This type of research is a quantitative study with a pure experimental method using a completely randomized design (CRD) method with three repetitions. This research was conducted in August-September 2021 at the IKK, FPP, UNP Catering Workshop. The type of data is primary data which is sourced from 4 limited panelists who are lecturers of Family Welfare Science concentration UNP Catering by filling out the organoleptic test format on the sample. Data were analyzed using Analysis of Variance (ANOVA), if Fcount > Ftable then continued with Duncan's test. The results showed that there was a significant effect on the quality of the texture (spongy). The highest overall achievement score is the round shape with a diameter of 2cm, which is 3.17 (0% and 30%), the uniformity shape is 3.17 (40% and 50%), the white color is 3.25 (30%), and has a distinctive aroma. tilapia is 3.25 (30%), chewy texture is 3.67 (50%), savory taste is 3.33 (0% and 30%).